Brexits Economic Ripple Effect: A Study of Migrant Entrepreneurs in Rural Scotland (Global Journal of Management and Business Research, 2024)
This research delves into the intricate economic repercussions of Brexit on migrant entrepreneurs and host rural communities in Scotland Data collection employed a combination of 275 questionnaires distributed across 10 rural areas and in-depth insights drawn from a total of six focus group discussions Specifically three focus groups were conducted with migrant entrepreneurs operating businesses in rural areas offering a profound exploration of their unique challenges experiences and perspectives Additionally three separate focus groups were conducted with the host communities encompassing rural residents and third-party stakeholders including local government representatives and community organizations The questionnaire yielded responses from a diverse sample with 115 valid responses after rigorous data cleaning The research utilizes a mixed-methods approach intertwining quantitative and qualitative analyses The quantitative analysis employs a non-parametric Kruskal-Wallis H test to examine the disparities in perceptions of Brexit s economic impact between migrant entrepreneurs and host rural communities across the 10 surveyed rural areas
Keywords: brexit; economic impact; migrant entrepreneurs; rural scotland; mixed- methods; non-parametric analysis